Effectiveness Of Pipe Installation for The Milking Process Using a Milking Machine - Zainul Arif, Muamar; , Novi Sukma Drastiawati; Kurniawan, Wahyu Dwi; Budijono, Agung Prijo; Utomo, Wahyu Mulyo (Proceeding of International Joint Conference on UNESA, 2024)
Thedemand for cow’s milk is strongduetothe size ofthemarket, which will result in longer milking times. Fatigue is a frequent occurrence in the industrial process, particularly the milking process, when individuals still actively use their hands. Due to this, the production procedure is inefficient, and the output is likewise constrained. making a milk can, a vacuumtube, and a hose-equipped mechanized milking equipment.Creating an automatic milking machine equipped with a milk can, a vacuumtube, and a hose. The method used in this study is numerical calculation study of water flow rate and head loss inside the pipe. This is used to know more about characteristic of two configuration pipe installation. The first one is pipe configuration 7m – 1.2m – 1.2m. The second one is pipe configuration 10m – 1.2m – 1.2m. The characteristic of the pipe configuration 7m – 1.2m – 1.2m and pipe configuration 10m – 1.2m – 1.2m as follows : 1) The quantity of fluid flow vs pipe length configuration 7m – 1.2m – 1.2m is Q = 0,235 m/s^3. The quantity of fluid flow vs pipe length configuration 10m – 1.2m – 1.2m is Q = 0,235 m/s^3 also. Because the diameter of the pipe is same 2 inches. The difference lies in the length of the pipe. 2) The head loss of 7m length for laminar flow is HL = 0.530m and for turbulent flow is HL = 0.361m. The head loss of 1.2m length for laminar flow is HL = 0.091m and for turbulent flow is HL = 0.062m. 3) The head loss of 10m length for laminar flow is HL = 0.756m and for turbulent flow is HL = 0.516m. The head loss of 1.2m length for laminar flow is HL = 0.091m and for turbulent flow is HL = 0.062m